Of Mice and Men: On the Origin of XMRV - Van Der Kuyl, Antoinette C.; Cornelissen, Marion; Berkhout, Ben (Frontiers in Microbiology, 2011)
The novel human retrovirus XMRV (xenotropic murine leukemia virus-related virus) is arguably the most controversial virus of this moment. After its original discovery in prostate cancer tissue from North American patients, it was subsequently detected in individuals with chronic fatigue syndrome (CFS) from the same continent. However, most other research groups, mainly from Europe, reported negative results. The positive results could possibly be attributed to contamination with mouse products in a number of cases, as XMRV is nearly identical in nucleotide sequence to endogenous retroviruses in the mouse genome. But the detection of XMRV proviruses in prostate cancer tissue proves it to be a genuine virus that replicates in human cells, leaving the question: how did XMRV enter the human population? We will discuss two possible routes: either via direct virus transmission from mouse to human, as repeatedly seen for e.g. hantaviruses, or via the use of mouse-related products by humans, including vaccines. We hypothesize that mouse cells or human cell lines used for vaccine production could have been contaminated with a replicating variant of the XMRV precursors encoded by the mouse genome.